Assessment and management of chronic obstructive pulmonary disease in the emergency department and beyond. (August 2011) - Rowe, Brian H; Bhutani, Mohit; Stickland, Mike K; Cydulka, Rita
Acute exacerbations of chronic obstructive pulmonary disease (AECOPDs) are common, can result in emergency department presentation and often result in hospitalization. After confirming the diagnosis and treating comorbidities, management of severe AECOPD includes bronchodilators, systemic corticosteroids, antibiotics, noninvasive ventilation and, occasionally, endotracheal intubation. Once discharged, delayed follow-up and suboptimal management often occurs. Antibiotics, systemic corticosteroids and optimization of nonpharmacological interventions (e.g., smoking cessation, immunization and pulmonary rehabilitation) are important discharge considerations. Improving linkages to primary providers who adhere to management involving a pharmacological and nonpharmacological evidence-based treatment plan is critical to preventing future AECOPDs, reducing healthcare utilization and maintaining the quality of life of patients following an AECOPD.